Using 3D design technology and a combination of carbon fiber and 16% HGM epoxy resin, female troops are wearing bulletproof vests - Agnes Sprakezia Lubis; Sovian Aritonang; Raditya Faradina; Vishal R Panse (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2024)
Women are becoming more active in the defense industry. Since the morphology of the female body differs from that of the male during military activities, it is required to modify personal protection equipment to accommodate the female body shape. According to a literature review, a survey of a sample of female soldiers from different nations revealed that they felt the impacts of breast soreness when running, as well as a sense of "distorted breasts" and breathing difficulties. The woman's petite frame and the bulky, hefty bulletproof jacket both draw criticism for their respective dimensions. Using 3D design technology, a female mannequin with a 95B breast size was scanned in order to create a bullet-proof vest that is tailored to the contour of a woman's body. Changes in the breast's contour, which affect changes in the surface point parameters, result in adaptive breasts. Utilizing a combination of carbon fiber and 16 percent HGM epoxy, bullet-proof vests can be modified to provide lightweight dimensions and have the benefit of good ballistic resistance. This results in a material that is 20 mm for thick, 1,348 kg in weight, and capable of absorbing 348.27 Joules of energy from bullets. The results of this research are not optimal, so developments are needed in further research.